Factors that Influence the Academic Success of College Athletes Participating in the National Association of Intercollegiate Athletics - Katie Moleski; B. David Ridpath; Lijing Yang (Journal of Intercollegiate Sport, 2023)
The purpose of this research is to conduct an exploratory study examining factors that influence the academic success of college athletes participating in the National Association of Intercollegiate Athletics (NAIA), a subject that has not been empirically studied. For this study, academic success defined as retention and graduation, represents the dependent variables of interest. Additionally, this study examines actors influencing academic success including institutional financial aid, background characteristics (race, gender), college experience (GPA, residential housing), athletic characteristics (sport, athletic expenses), organizational structure, and participation as a varsity or non-varsity athlete. This study uses institutional data from 2019-2020 NAIA’s Return on Athletics (ROA) initiative, and data from the Integrated Postsecondary Education Data System (IPEDS). Logistic regression is used to answer two research questions exploring the factors that influence NAIA college athlete success. Findings indicate athletes are retained at a high rate in comparison to available NAIA data, but certain sub-groups may be at risk for attrition. Specifically, non-varsity athletes, athletes with a grade point average below 3.0, or those who have been enrolled less than two years.